New records and new species of Ophiuroidea (Echinodermata) from Lifou, Loyalty Islands, New Caledonia - Stöhr, Sabine (Zootaxa, 2011)
New Caledonia is a species-rich region that has been the focus of biodiversity research for over 40 years. The expedition “Atelier Lifou 2000” collected benthic fauna at the island of Lifou, Loyalty Islands, New Caledonia, in November of 2000. This is a taxonomic account of the brittle stars found. 94 species were identified, 51 of them new for the region, and seven new to science, increasing the total number of species known from the New Caledonia region to 204. New species are described in the genera Squamophis, Astroceras, Astrogymnotes, Ophiochondrus, Ophiomoeris, Ophiozonella and Amphipholis. Three species and a subspecies are revised, one of them placed in a new genus. The taxonomic status of Euryale Lamarck, 1816, a junior homonym of Euryale Péron & Lesueur, 1810 (a medusa), is stabilized by formally establishing precedence over the senior name.